Produksi Pati Termodifikasi dari Beberapa Jenis Pati - Erika, Cut (Jurnal Rekayasa Kimia & Lingkungan, 2010)
Starch is modified for three reasons. First, modified starch provides functional attributes in food applications that native starches normally cannot provide. Second, starch is abundant and readily available. Third, starch can provide an economic advantage in many applications. Process for the production of modified starch comprised the steps of (1) extracting starch from potato and sweet potato, and (2) modifying the starch to produced pre-gelatinized, acid modified, and cold water swelling starch. Tapioca gives the best performance when modified by pre-gelatinization and cold water swelling. The characteristic of the pre-gelatinized tapioca were swelling power 979,782%, water holding capacity 480,391%, moisture contents 8.48%, ash content 0,006%, dan yield 93,358%.Keywords: acid modified, cold water swelling starch, modified starch, pre-gelatinized